Penerapan Keadilan Restoratif Dalam Tindak Pidana Lalu Lintas - Kiriwenno, Refliani Drevantly; Sopacua, Margie Gladies; Ubwarin, Erwin (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The traffic accident that happened to DH (18), a member of the community from Laha Village, Teluk Ambon District, was declared dead after the motorcycle he was driving was hit by a car driven by an RT is a crime that is not a minor crime as stated in the State Police Regulations Republic of Indonesia Number 8 of 2021 concerning the Handling of Crimes Based on Restorative Justice, however this case was resolved peacefully, and investigators stopped the legal process.Purposes of the Research: The research objective at this writing is to examine and discuss the concept of restorative justice in the criminal justice system. Reviewing and discussing restorative justice that can be applied to traffic crimes that result in the death of victims.Methods of the Research: The research method used is empirical juridical research, which is a type of research used to look at legal aspects of social interaction in society.Results of the Research: The concept of Restorative Justice is applied in the Criminal Justice System, for example the National Police Uses the National Police to issue a Circular of the Chief of Police Number: SE/8/VII/2018 dated 27 July 2018 in order to realize the public interest and a sense of justice for people who do not yet have a legal basis and can be used as a guideline for its implementation and in order to realize the non-uniform understanding and application of restorative justice within the Police. In its development, the National Police issued Republic of Indonesia National Police Regulation Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice. Restorative Justice can be applied in Traffic Crimes that result in the victim dying, using the basis of the Chief of Police Circular Letter Number: SE/8/VII/2018 which is then amended by Republic of Indonesia National Police Regulation Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice, and Article 236 of Law Number 22 of 2009 concerning Road Traffic and Transportation, as the basis for application.